If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(1 + -5x) = -182 (1 * -7 + -5x * -7) = -182 (-7 + 35x) = -182 Solving -7 + 35x = -182 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 35x = -182 + 7 Combine like terms: -7 + 7 = 0 0 + 35x = -182 + 7 35x = -182 + 7 Combine like terms: -182 + 7 = -175 35x = -175 Divide each side by '35'. x = -5 Simplifying x = -5
| 6(5x-7)=-19 | | -4(8+y)=90 | | 10-2r=3(5r-8) | | 7(x-6)=-2x+21 | | n+9=5*4 | | 4r+14-r-6= | | 3x=180-(2x+10) | | 2(83)-7x=x+16 | | 6(r+6)=18 | | 180-3x=(2x+10) | | 6(x-4)=3(x-4) | | 16k+21=-5f+48 | | 3x-5+2x+4=9 | | 2.5x+25=3 | | 2(3x-1)=4x+9 | | 2x+12=3x-1-15 | | 8(5+5k)=-160 | | 41-g=42 | | y-1=8/5(x-11) | | 32x=15x | | 3x+25=2.5 | | 8x+7=31-x | | -3m+11=-7(-5+m) | | -7(7n+1)+5n=38+n | | 6(8-7n)+2n=168 | | 10(2x+6)=-4(1+3x) | | 10x+8x=98 | | -30+2x=3(3x+4) | | -4-5n=3(5n-8) | | 45+54+x=180 | | 36+7n=-7+6(4n-7) | | -5(-8x-3)+2=-19+4x |